Mechanism for the Morphological Change from Trenching to Pitting around Intermetallic Particles in AA1050 Aluminum. Issue 2 (1st January 2019) - Kakinuma, Hiroshi; Muto, Izumi; Oya, Yoshiyuki; Kyo, Yoshihiko; Sugawara, Yu; Hara, Nobuyoshi
Abstract : The mechanism of trenching and pitting at intermetallic particles in AA1050 aluminum was investigated by open circuit potential measurements and microscopic polarization measurements, and the role played by the two types of intermetallic particles, Al-Fe and Al-Fe-Si, in this process was determined. Trenching was observed only around the Al-Fe-Si particles in the naturally aerated 0.1 M NaCl solution. Under the anodic polarization of AA1050 in naturally aerated 0.1 M NaCl, a crystallographic pit was initiated in the trench. However, neither trenching nor pitting occurred in the citric-citrate buffer with 0.1 M NaCl under naturally aerated conditions. Trenching was confirmed to be the result of the local alkalization induced by the oxygen reduction reaction on the particles. Micro-scale polarization showed that trenching occurred around the Al-Fe-Si particle from −0.9 to −0.6 V and did not occur above −0.5 V. While the surface of pure Al dissolved at pH 14 in 1 M NaCl, the corrosion morphology was different from pitting. Crystallographic pits occurred when the pure Al was immersed in 1 M NaCl at pH 0.0 after preimmersion in 1 M NaCl (pH 14). It was concluded that the change in local pH from alkaline to acidic triggers the morphological change from trenching to pitting.